Exploring the potential of small molecules of dual c-Met and VEGFR inhibitors for advances and future drug discovery in cancer therapy - Sachin A. Dhawale; Arundhati V. Deokar; Momin Aaliya Firdous; Madhuri Pandit; Minal Y. Chaudhari; Sameer B. Salve; Madhuri Khandgaonkar; Mahesh Parwe; Rupesh Khalse; Shruti G. Dake; Siddharth H. Chatse; Ganesh G. Tapadiya (SpringerOpen, 2024)
Abstract Background Cancer is uncontrolled cell proliferation that has the potential to invade other tissues and cells. The first three most prevalent cancers are breast, lung, and colon cancer. The widest family of kinase enzymes is receptor tyrosine kinases (RTKs) which are aimed by several chemotherapy medicines. The vascular endothelial growth factor (VEGFR), a well-known type IV tyrosine kinase receptor, is an effective biological target for the development of angiogenesis-related cancer treatments. The hepatocyte growth factor (also known as mesenchymal-epithelial transition factor) triggers the activation of the c-Met tyrosine kinase receptor, which controls several biological processes including cell division, survival, and proliferation. Main body In this review, we summarized the various dual inhibitors of VEGFR and c-MET receptors which are active for therapeutic action against cancer. Combination of some VEGFR and c-Met inhibitors also shows synergistic action. The developed dual inhibitors of VEGFR and c-MET such as quinolones and quinazolines derivatives, pyridine and pyrimidine derivatives, oxindole moiety and triazine derivatives are most potent for the same. Dual inhibitors of VEGFR and c-MET hold significant promise in improving cancer therapy by enhancing treatment efficacy, reducing resistance, and potentially improving patient outcomes. Clinical trials are currently being conducted on a few of them and other compounds are being under investigation. Inhibiting VEGFR and c-Met pathway activity will be discussed as novel therapeutic strategies for advanced development in treating cancer. The research progress in this review is fetched up to the current year. Conclusion Apart from the development of cancer treatment still cancer is listed as a deadly disease, due to its toxicity and resistance to treatment. Hence, the novel approach is necessary to overcome the cancer. The VEGFR and c-MET inhibitors as dual inhibitors may be more significant in future clinical anticancer treatments.